Turismemorfosis: Tahapan selama seratus tahun perkembangan dan prediksi pariwisata Bali - I Putu Anom; Ida Ayu Suryasih; Saptono Nugroho; I Gusti Agung Oka Mahagangga (Jurnal Kajian Bali (Journal of Bali Studies), 2017)
Bali Tourism has grown for the hundred years, but there has never been a mapping of its developmental stages and its future predictions. This article examines the development of tourism in Bali in the past, present, and future predictions, as well as discourse in each stage. Data were collected by literature study, observation, and in-depth interviews with diachronic informants. The main theory used is critical evolution and genealogy. This article offers a model of tourismemorphosis as a stage of tourism development along with its paradigms including the introduction stage, reaction stage, institutional stage, and compromise stage. The prediction of future Bali tourism development is to remain at the compromise stage with the transtourism paradigm that is paradigm with the effort of adjusting all tourism components to respond to the big and rapid changes of tourism globally. Always compromise, Bali tourism stakeholders in the future are still demanded to be creative in the future, customary government, market dynamics, IT development, customs, and religious rituals to survive or even move forward.